Computed tomography pulmonary angiography is overused to diagnose pulmonary embolism in the emergency department of academic community hospital - Mohammed Osman; Suresh Kumar Subedi; Azza Ahmed; Jahangir Khan; Thair Dawood; Carlos F. Ríos-Bedoya; Ghassan Bachuwa (Journal of Community Hospital Internal Medicine Perspectives, 2018)
Background: Pulmonary embolism (PE) is a common disease in the USA responsible for up to 10% of hospital mortality. Modified wells score (MWS) and D-dimer assay are used to categorize patients into high or low probability of PE. Patient with high probability need Computed tomography pulmonary angiography (CTPA), while patients with low probability and low D-dimer can safely forgo the CTPA. Objectives: The aim of this study was to investigate the rate of inappropriate CTPA use in the emergency department of a community teaching hospital. Methods: A retrospective chart review of adult patients who underwent CTPA for suspected PE in the emergency department for 2015 was done. CTPA use was considered inappropriate if MWS was less than or equal to 4 and D-dimer was either not ordered or its value was less than 500 μg/L. Bivariate analysis with Fisher’s exact tests and Student’s t-tests as well as multivariate logistic regression analysis were done to examine relationship between study explanatory variables and study outcome. Results: 295 patients were included in the study. The mean age was 51.2(±14.5) years, 68.8% were females. The prevalence of PE was 5.4% and 41% of the CTPAs -were inappropriately ordered. Males were twice (OR 2.1; 95% CI 1.2, 3.6) as likely as females to have an inappropriately ordered CTPA after controlling for a high MWS, age, and tobacco history. Conclusion: CTPA is overused to diagnose PE in the emergency department. Quality improvement projects are needed to encourage physicians to adhere to the current guidelines.